Do Investors Value Auditor Involvement in Non‐GAAP Reporting? - Lamoreaux, Phillip T.; Matkaluk, Lauren; Sheneman, Amy G. (Journal of Accounting Research, 2026)
ABSTRACT This paper examines investors’ perceptions of auditor involvement in non‐GAAP reporting as captured by non‐GAAP disclosures in 10‐K filings. We find that firm‐years with auditor involvement in non‐GAAP reporting have higher CARs, lower bid–ask spreads, lower stock volatility, and lower abnormal trading volume on 10‐K filing dates. To sharpen identification of auditor involvement, we hand‐collect non‐GAAP measures and reconciliations for S&P 500 firms and identify which exclusions reconcile directly to the audited financial statements. As the percentage of exclusions that reconcile directly to the audited financial statements increases, bid–ask spreads and stock volatility on 10‐K filing dates decrease. We find that the results are not driven by strategic reporting or managers’ responses to perceived litigation risk. This study provides new insights into non‐GAAP disclosures outside of earnings announcements, which have been largely ignored in prior literature. Collectively, our results suggest investors value auditor involvement in non‐GAAP reporting and inform policymakers and standard setters considering the usefulness of assurance over non‐GAAP measures.